The brown citrus aphid, Toxoptera citricida - Yokomi R.K. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
This article describes various aspects of the brown citrus aphid, Toxoptera citricida : identity, hosts, geographic distribution, biology and ecology, natural enemies, pest significance (economic impact), identification and control.